EVALUASI PENGELOLAAN ALOKASI DANA DESA DALAM UPAYA MENINGKATKAN PEMBANGUNAN DAN PEMBERDAYAAN MASYARAKAT - Haryani, Deffi (Universitas Gajah Putih, 2024)
The Indonesian government is currently making outstanding efforts to enhance national, local, metropolis, and village improvement to gain stability and fairness in development. Allocation of Vilthe large price range is the right of the village as district/metropolis governments have the proper to reap trendy Allocation funds (DAU) and unique Allocation price range (DAK). The expected effects of the Village Fund Allocation are the advent beta the village budget to finance village government packages, both village operations, and village community empowerment to improve village authorities services, improvement, governance, and network empowerment. Goal to determine the effectiveness of the Village Fund Allocation policy in Marga Sungsang Village, Banyuasin II District, Banyuasin Regency, South Sumatra visible from the context, input, manner, and product and evaluation of the extent of Village Fund Allocation in the control category technique: this is quantitative research with a cross-sectional method drawing near. Result: typical, this size has a big move-sectional scale, particularly: the overall context is 79.05 the general input is 76.10, the overall process is eighty one.45 and the overall product is seventy six.88. limitations: based on the researcher's direct theel in the research process, there are numerous barriers, along with the range of respondents is simplest 33 people, direction, twhichiswhichetheless not enough to describe the state of aff, airs and the item of studies which specializes in the effectiveness of the add program in terms of context, input, method, and product and level of control of Village Allocation within the class of Sungsang Marga Village, Bnayausin II District, Banyuasin Regency, South Sumatra. Contribution: For Sungsang Marga Village, Banyuasin II place, South Sumatra Banyuasin, to take advantage of extra village subsidies and increase similarly development of network development and empowerment. F, or the aTher this research to boom knowledge and expand peproperlyon andregardingal inregardinghe problem of coping with the allocation of village budget to solidarity improvement and empowerment. For the Alma mater, the outcomes of this lexpecteddexpectedato dd new references from the analysis of add management in improving network improvement and empowerment.